Males of the solitary bee Anthophora plumipes have longer tongue, larger ocelli, and higher fluctuating asymmetry in more urbanised habitats - A. Ferrari; C. Polidori (The European Zoological Journal)
Urbanisation, leading to the reduction and fragmentation of green areas and an increase in temperature (urban heat island effect), is known to be a strong driver of intraspecific phenotypic variation in wild bees. However, the effects of urbanisation on many functionally relevant morphological traits are still unstudied or debated. Here, males of the ground-nesting, solitary bee Anthophora plumipes were sampled at nine sites in the metropolitan city of Milan (Italy). The aim was to test variation in body size, head width, compound eye size, ommatidia density, antenna length, median ocellus size, galea length (proxy for tongue length), wing area, wing loading, wing aspect ratio, and wing fluctuating asymmetry along an urbanisation gradient. We found some of these traits to significantly shift across the gradient. Bees in hotter (urban) areas had longer galea, agreeing with previous community-level studies showing more long-tongued wild bee species in urban areas. This may suggest that urbanisation filters for longer mouthparts at both species and individual level. Ocelli were larger in males from more urbanised sites, perhaps improving navigation in more fragmented habitats. Finally, bees in greener (less urban) areas had also lower wing fluctuating asymmetry, suggesting that urbanisation may act as an early-life stressor in A. plumipes. None of the other analysed morphological traits varied with urbanisation, which contrasts (especially for body size and wing size) with several previous studies on other bee species in urban contexts. Such patterns highlight how difficult is to draw generalisable trends regarding the effects of urbanisation on wild bees. Nonetheless, this study provides the first evidence of such effects on rarely studied morphological traits (mouthparts, ocelli) in male bees.